Destiny, Miracle Healers and Magical Intervention: Vernacular Beliefs on Involuntary Childlessness in Estonia - Reet Hiiemäe (Journal of Ethnology and Folkloristics)
The article focuses on the dynamics of contemporary beliefs related to involuntary childlessness. Firstly, the methodological issues of collecting source material on delicate matters and the advantages of anonymous and narrative presentation modes in certain contexts will be discussed. Secondly, conclusions drawn from the collected material, i.e. the temporary and changeable nature of those beliefs, their relations with the mass media, the social and the individual aspects and the motifs of guilt and supernatural punishment in the context of identity issues will be presented, concluding that such belief-based models of explanation and help-seeking eventually function as a mental self-defence mechanism.